MENJALIN KERJA SAMA PEMERINTAH DAN MASYARAKAT DALAM PEMBANGUNAN DI KALURAHAN CONDONCANTUR - Fidilu, Marsiana; Herlince, Margaretha; Maria, Ina; Muhammad, Adji Suradji (MAJU : Indonesian Journal of Community Empowerment, 2024)
This journal discusses government and community cooperation in development in the Condongcatur sub-district, namely encouraging community participation to build their own village and so that it becomes better and community involvement must be active in development. Starting from the results of the interview, the author was interested in taking this title in order to find out how community participation in development in the Condongcatur Village, Kapanewon Depok, Sleman Regency, Yogyakarta Special Region. To explain community participation in development, this writer uses a qualitative descriptive research method. The data collection method was carried out through interviews and observation with the selection of informants according to the aims of this researcher. The Condongcatur sub-district government and encouraging community participation in general already understand the development activities that are carried out every year. Community participation is quite active, but has not been able to provide comprehensive data and information. In implementing the strategy, the Condongcatur urban village government experienced obstacles which included a lack of budgetary funds and not optimal public awareness.